Economics of Organic Vs Inorganic Carrot Production in Nepal - Adhikari, Raj Kumar (Journal of Agriculture and Environment, 2009)
During February-April 2008, a study was conducted to compare the yield and economics of organic and inorganic carrot production and its profit volume in Chitwan district of Nepal. Face to face interview method was used to collect the primary information from randomly selected organic and inorganic carrot producers. Among the cost components, per unit cost on female labor and organic fertilizer were found to be higher in organic production system where as higher per unit cost on seed, tillage operation and male labor were found in inorganic production system. Higher cost and higher revenue was found in inorganic production system but higher benefit cost ratio was found in organic production system. This revealed that adoption of organic carrot production system was economically profitable than inorganic production system. Key words: Benefit cost ratio; Carrot; Cost; Gross margin; Organic agriculture The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 27-33